Effects of carbon sources, plant growth regulators and inoculum size on Citrus suhuiensis cell suspension culture growth - Mohamad Puad, Noor Illi; M. Fathil, Nur Alia; Amid, Azura; Azmi, Azlin Suhaida (Journal of the Malaysian Society of Applied Biology, 2020)
Cell suspension culture of Citrus suhuiensis (C. suhuiensis) was established to determine the best growth condition based on the effects of carbon source, plant growth regulators (PGRs) and inoculum size. Friable callus from the cotyledon explant was used to initiate the cell suspension cultures. Murashige and Skoog (MS) medium supplemented with 50 g/L glucose achieved the highest cell dry weight (CDW) and μmax of 23.2 g/L and 0.47 h-1 respectively compared to glucose at 30 g/L and other carbon sources. For PGRs effects, 0.5 mg/L 2,4-dichlorophenoxyacetic acid (2,4-D) gave the highest amount of CDW and μmax; 11.91 g/L and 0.32 h-1. Furthermore, the inoculum size at 10% (v/v) gave the maximum CDW and μmax of 15.45 g/L and 0.71 h-1 respectively compared to 20% (v/v) and 30% (v/v) of inoculum. The results achieved can be used for further statistical optimization of C. suhuiensis cell suspension culture growth parameters in which the interactions between those parameters can be further studied and understood.